HUBUNGAN EXPLOSIVE POWER OTOT TUNGKAI DENGAN KEMAMPUAN LOMPAT JAUH SISWA KELAS V SDN 011 KEPALA PULAU KABUPATEN KUANTAN SINGINGI - Darmis, Darmis; Saripin, Saripin; Agust, Kristi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract, Based on observations the author did in class V SDN 011 Kepala Pulau seen that in doing the long jump which is obtained by the students is still not good, it is presumably because of leg muscle explosive power of students is still lacking. Therefore, researchers wanted to show whether there is a relationship ecplosive limb muscle power with the ability to long jump. This research was conducted using Correlational where according Sugiyono (2010: 228) the correlation technique is used to find the relationship and prove the hypothesis relationship between two variables when the second data interval or ratio variable shaped, and the source of the data from two or more variables are equal. The sample in this study were students of SDN 011 male and femaleof the head of the island amounted to 15 people with a total sampling technique. The data in this study were obtained from a standing broad jump test to measure limb muscle explosive power and long jump test. Liliefors normality test using the results of normal distribution of data. Furthermore, the data was analyzed using product moment correlation test and found to male students rhitung 0:22 value smaller than rtabel = 0754, in other words there is no relationship of leg muscle explosive power with the ability lomapt away, while the female students gained grades rhitung = 0.71sedangkan value rtabel = 0.70 can be concluded that there is a relationship of leg muscle explosive power with the ability to long jump schoolgirl daughter of SDN 011 Kepala Puaau.Keywords: Explosive Power Legs Muscle, Long Jump